THE IMPLEMENTATION OF ONLINE LEARNING IN ELEMENTARY SCHOOL OF SOUTH KALIMANTAN PROVINCE DURING COVID-19 - Dina Huriaty; Rahidatul Laila Agustina; Hajjah Rafia Hajjah Rafia; Wulida Makhtuna; Hidayatul Adha Yanie; Lindawati Lindawati; Rizki Aulia Rahmah; Rizky Malia (Proceeding International Conference on Digital Education and Social Science, 2022)
This study aims to describe the implementation of online learning in elementary schools in South Kalimantan which includes planning, implementation, evaluation, and supervision. This research was a descriptive research. The samples of this study were 4 principals, 8 teachers, 180 students in elementary schools in three districts/cities in South Kalimantan. Data collection instruments were documentation and questionnaires and the data were analyzed using quantitative and qualitative data analysis techniques. The results of research on each component studied were as follows. (1) Planning: the preparation in online learning is carried out by the principal by providing directions to teachers, staff, students and parents so that they can prepare applications for teaching and learning activities and other tools that support online learning. (2) Implementation: school principals monitor teacher performance in face-to-face online learning at schools. The teachers make various assessments in each class, at the end of each material for class III and at the end of the month for class V, while students state that they are ready with applications for online learning. Applications that are often used by teachers are WhatsApp and Google Classroom. (3) Assessment: the principals ask for cooperation of teachers, students and parents. Teachers assess online learning outcomes with multiple-choice tests that are carried out every semester through PTS (Middle Semester Assessment) and PAS (Final Semester Assessment). (4) Supervision: the principals carry out teacher performance evaluations so that the implementation of online learning goes well. If there are obstacles, a solution will be arranged to resolve the problem.